Clima organizacional de discentes e servidores de pós-graduação de uma instituição pública de ensino superior - Moro, Angélica Balconi (2013)
Evaluating the organizational climate is a tool that provides knowledge about the work environment with information that managers may use strategically to make sense of scenario changes. This allows them to apply corrective measures, especially for improving quality and productivity gains, thus ensuring the success in the evaluation process from CAPES. Therefore, the objective of this study was to identify related factors to organizational climate that influence the workplace of students and employees of the Post-Graduate Program (PPGs) of a Public Institution of Higher Learning. For this purpose, we carried out a climate research by means of a questionnaire based on models of Rizzatti (2002) and Luz (2003) and adapted to the reality of each program that it was intended to investigate. The results obtained, through the perception of the academic public, validated a set of components and respective indicators to investigate the organizational climate for learners and teachers of PPGs studied. On the basis of the analysis carried out, we conclude that the academic community notices the organizational climate factors that influence the work environment similarly in different dimensions. Students, teachers and technical-administrators evaluate the workplace in a very satisfactory way, mainly in relation to the activity which play in programs, resulting commitment, hard work, and dedication in carrying out tasks. This provides motivated behavior, especially between students and teachers, where the chances of placing on the market, growth opportunities, and the curriculum represent a stimulus in this process, which otherwise generates competition between colleagues, especially between different groups within the PPGs. On the other hand, the relationship between colleagues of the same workgroup shows a climate of integration, cooperation, and friendship. However, related factors include interpersonal relationships between different groups of work, working conditions, financial support for research and events, and the quantity of hours of class. Additionally, disciplines and work overload and topics pertaining to managers negatively interfere in the workplace, compromising the establishment of an organizational climate. In this way, the aim of this study has been reached, to the extent that it has contributed information and useful research tools for effectively managing process PPGs. With this information, the managers may detect the possible causes and consequences of occurring problems, and may apply corrective measures, especially in improving the quality and academic productivity, which will contribute to the success in the process of program evaluation from CAPES. Also, this will help the development of studies by improving the various processes that make up not only the study programs of IES, but also others who wish to avail themselves of this research instrument.